Comparison of the General Threshold Model of Survival and Dose–Response Models in Simulating the Acute Toxicity of Metals to Danio rerio. (5th September 2019) - He, An; Liu, Xinyong; Qu, Liang; Gao, Yongfei; Feng, Jianfeng; Zhu, Lin
Abstract: We exposed zebrafish ( Danio rerio ) to different concentrations of lead and cadmium, and monitored them for survival at 24, 48, 72, and 96 h. Metal toxicity was predicted and compared using the dose–response and general threshold survival models in terms of required data sets, fit performance, and applicability. Environ Toxicol Chem 2019;38:2169–2177. © 2019 SETAC.